2021
DOI: 10.54659/ulum.974533
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Evaluation of the Experiences of Faculty Members and Students at the Faculty of Theology/Islamic Sciences regarding Distance Education System during the Covid-19 Pandemic

Abstract: During the Covid-19 pandemic, lectures have been delivered through distance education since the Spring Semester of the 2019-2020 Academic Year at the faculties of theology/Islamic sciences, as has been the case at all educational levels in our country. The purpose of this study is to investigate the perceptions of the students and faculty members of the faculty of theology/Islamic sciences, regarding the impacts of distance education on higher religious education, its advantages and disadvantages, along with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
0
0
Order By: Relevance
“…Another study investigated the perceptions of students and faculty members regarding the effects of remote education. The study revealed that most respondents considered remote learning an excellent alternative to traditional instruction (Yazıbaşı et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another study investigated the perceptions of students and faculty members regarding the effects of remote education. The study revealed that most respondents considered remote learning an excellent alternative to traditional instruction (Yazıbaşı et al, 2021).…”
Section: Discussionmentioning
confidence: 99%